Tuneable anisotropy and magnetism in Sn2Co3S2−xSex – probed by 119Sn Mößbauer spectroscopy and DFT studies12. Issue 36 (28th September 2015) - Weihrich, Richard; Yan, Wenjie; Rothballer, Jan; Peter, Philipp; Rommel, Stefan Michael; Haumann, Sebastian; Winter, Florian; Schwickert, Christian; Pöttgen, Rainer
<x xml:space="preserve">Abstract</x> Magnetic coupling of spins in and between Co-Kagomé layers is studied from experiment and theory for Sn2Co3S2−xSe2.